Effectiveness of an integrated 4T intervention test, treat, talk and track in mitigating anemia among tribal communities in Telangana, India - Vikram Gupta; Nehana Neeladdi; Venkat Rao Mantha; Bhagirath Gop; Dhanaraj Chittapur (International Journal Of Community Medicine And Public Health, 2026)
Background: Anaemia affects over 1.6 billion people worldwide, with India bearing a disproportionate burden despite five decades of national programming. Telangana’s 70% prevalence exceeds the 67.1% national average, with tribal districts like Bhadradri Kothagudem suffering from poor dietary diversity, limited healthcare access, and socioeconomic disadvantages. This study evaluated whether an integrated "4T" intervention- Test, Treat, Talk, and Track - could reduce Anaemia in this vulnerable population. Methods: A community-based longitudinal study was conducted in Laxmidevipally Mandal, Bhadradri Kothagudem, covering 1,228 households across 16 villages with a baseline population of 5,291. Haemoglobin levels were screened using the non-invasive EzeCheck device. Anaemic participants received targeted medical treatment, Behaviour Change Communication (BCC), and Nutri-kits for home kitchen gardens. Results: Following quarterly follow-ups and matched endline analysis, overall anaemia prevalence dropped significantly from 64.59% to 53.75% (p